MODERN METHODS OF TEACHING ENGLISH BASED ON ESP (ENGLISH FOR SPECIFIC PURPOSES) - Abdullayeva Sevara Odashaliyevna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article examines modern methods of teaching English for Specific Purposes (ESP) in higher and vocational education. It highlights the significance of learner-centered instruction, needs analysis, communicative language teaching, task-based learning, project-based learning, digital technologies, artificial intelligence, authentic materials, and competency-based assessment in developing learners’ professional communicative competence. The study emphasizes that ESP enables students to acquire language skills directly related to their academic and occupational fields, thereby increasing their employability and professional effectiveness.